IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU DI ERA KECERDASAN BUATAN DAN DIGITALISASI PENDIDIKAN STUDI KASUS DI SMP AL FALAH - Novrizal; Teni Pursina; Ade Sumartini; Elis Ela Sumyati; Lilis Suwandari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The rapid development of Artificial Intelligence (AI) and the digitalization of education require teachers to strengthen their pedagogical competence in order to effectively integrate technology into the teaching and learning process. However, in practice, teachers demonstrate varying levels of competence in utilizing AI and digital technologies for planning, implementing, and evaluating learning activities. In addition, empirical studies examining the implementation of teachers' pedagogical competence in the context of AI integration at the school level remain limited, highlighting the need for further investigation. Therefore, this study aimed to analyze the implementation of teachers' pedagogical competence in the era of Artificial Intelligence and educational digitalization at SMP Al Falah. This study employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation involving the principal and five teachers. The data were analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that teachers had implemented pedagogical competence by utilizing various digital learning platforms and AI-based applications to develop lesson plans, create instructional media, design assessment instruments, and support differentiated learning. These practices improved the effectiveness of lesson planning, implementation, and evaluation. Nevertheless, differences in AI literacy among teachers, limited internet infrastructure, and the absence of school policies governing the systematic use of AI were still identified as major challenges. The study concludes that the integration of pedagogical competence, Technological Pedagogical Content Knowledge (TPACK), and AI literacy is essential for supporting educational transformation. Therefore, strengthening teachers' digital competence through continuous professional development and establishing school policies are necessary to ensure that AI is utilized optimally, ethically, and responsibly. ABSTRAK Perkembangan kecerdasan buatan (Artificial Intelligence/AI) dan digitalisasi pendidikan menuntut guru untuk memiliki kompetensi pedagogik yang mampu mengintegrasikan teknologi ke dalam proses pembelajaran. Namun, pada praktiknya masih ditemukan perbedaan kemampuan guru dalam memanfaatkan AI dan teknologi digital untuk merancang, melaksanakan, serta mengevaluasi pembelajaran secara efektif. Selain itu, kajian yang mengulas implementasi kompetensi pedagogik guru dalam konteks pemanfaatan AI di tingkat sekolah masih relatif terbatas, sehingga diperlukan penelitian untuk memberikan gambaran empiris mengenai kondisi tersebut. Oleh karena itu, penelitian ini bertujuan menganalisis implementasi kompetensi pedagogik guru di era kecerdasan buatan dan digitalisasi pendidikan di SMP Al Falah. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara, observasi, dan dokumentasi terhadap kepala sekolah dan lima orang guru, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldaña yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru telah mengimplementasikan kompetensi pedagogik melalui pemanfaatan berbagai platform pembelajaran digital serta aplikasi berbasis AI untuk menyusun perangkat pembelajaran, mengembangkan media, menyusun instrumen evaluasi, dan mendukung pembelajaran diferensiasi. Implementasi tersebut meningkatkan efektivitas perencanaan, pelaksanaan, dan evaluasi pembelajaran. Namun, masih ditemukan perbedaan tingkat literasi AI antar guru, keterbatasan infrastruktur internet, serta belum adanya kebijakan sekolah yang mengatur pemanfaatan AI secara sistematis. Penelitian ini menyimpulkan bahwa integrasi kompetensi pedagogik, TPACK, dan literasi AI merupakan faktor penting dalam mendukung transformasi pendidikan sehingga diperlukan penguatan kompetensi digital guru, pelatihan berkelanjutan, dan penyusunan kebijakan sekolah agar pemanfaatan AI berlangsung secara optimal, etis, dan bertanggung jawab.